The Influence of Situational Leadership and Motivation on the Performance of ASN at the Manpower, Transmigration, and Population Office of Central Sumba Regency - Anabuni, Andrias U. T.; Siahaan, Moni Y. (Journal of Practical Management Studies, 2025)
This study aims to analyze the influence of situational leadership and motivation on the performance of State Civil Apparatus (ASN) at the Manpower, Transmigration, and Population Office of Central Sumba Regency. This study uses a quantitative method with multiple linear regression analysis. The research sample consisted of 198 respondents from a total population of 248 civil servants. The research results show that both situational leadership and motivation significantly affect the performance of ASN. Adaptive situational leadership can motivate ASN, improve communication, and create a productive work environment. Motivation, both intrinsic and extrinsic, has also been proven to improve the performance of ASN. This study recommends that the relevant agencies develop responsive leadership strategies and enhance the motivation of civil servants to achieve optimal performance. Thus, the quality of public services and the achievement of organizational goals can be improved.